Effects of Respiratory Therapy (bagging) on Respiratory Function, Swallowing Frequency and Vigilance in Tracheotomized Patients in Early Neurorehabilitation - Frank, U.; Frank, K.; Zimmermann, H. (Pneumologie, 2015)
Objective: Tracheotomized patients often suffer from impairments in mucociliary clearance and limited capacities for active expectoration of secretions. We investigated the effects of a specific respiratory intervention method (bagging) for tracheotomized patients on respiratory parameters (pO2, pCO2, SpO2, respiratory rates), swallowing frequency, vigilance and secretion viscosity. Methods: The bagging method supports enforced mobilization and expectoration of secretions by application of a series of manual hyperinflations with a resuscitation bag during active inspiration and manual cough support on the chest. 30 tracheotomized neurological patients participated in a multiple-baseline study including a three-weeks intervention period and a follow-up measurement three weeks after termination of the treatment. Results: Most outcome parameters improved significantly during the intervention period: pO2 (p < .01), SpO2 (p < .01), respiratory rates (p < .01), swallowing rates (p < .01), and vigilance scores (p < .01). The quality of bronchial secretions improved in all participants. All effects were sustained up to the follow-up measurements. Conclusion: This preliminary data indicates positive effects for a respiratory intervention method (bagging) on respiratory function and additional respiration-related functions in tracheotomized neurological patients. This easy-to-learn and inexpensive method might expand the range of treatment options for tracheotomized and non-responsive patients.